PENGARUH PARTISIPASI MASYARAKAT DAN KEBIJAKAN PEMERINTAH TERHADAP KESEJAHTERAAN MASYARAKAT MELALUI KEBERLANJUTAN PARIWISATA NUSA PENIDA - Indrayani, Ni Kadek Ayu; Setiawina, N Djinar (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.04.TAHUN 2018DO - 10.24843/EEB.2018.v07.i04.p06, 2018)
The Government designed various development programs by improving the regional economic structure. Tourism Nusa Penida Island is an industry that is being developed by the Government of Klungkung Regency to improve the quality of life of the community. Based on that data this study is aimed to analyze:1) how are the influences of society participation and the role of government to the sustainable tourism in Nusa Penida; 2) how is the influence of sustainable tourism to the prosperty of society; and 3) do variable of society participation and the role of the government indirectly influence the prosperty  of society through the sustainable tourism in Nusa Penida.Sources of data are primary data obtained from the questionnaire, with the number of respondents as many as 98 people. The analysis tool used is SEM-PLS.